(p-2)(p+4)+(p-2)(p+6)=0

Simple and best practice solution for (p-2)(p+4)+(p-2)(p+6)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (p-2)(p+4)+(p-2)(p+6)=0 equation:


Simplifying
(p + -2)(p + 4) + (p + -2)(p + 6) = 0

Reorder the terms:
(-2 + p)(p + 4) + (p + -2)(p + 6) = 0

Reorder the terms:
(-2 + p)(4 + p) + (p + -2)(p + 6) = 0

Multiply (-2 + p) * (4 + p)
(-2(4 + p) + p(4 + p)) + (p + -2)(p + 6) = 0
((4 * -2 + p * -2) + p(4 + p)) + (p + -2)(p + 6) = 0
((-8 + -2p) + p(4 + p)) + (p + -2)(p + 6) = 0
(-8 + -2p + (4 * p + p * p)) + (p + -2)(p + 6) = 0
(-8 + -2p + (4p + p2)) + (p + -2)(p + 6) = 0

Combine like terms: -2p + 4p = 2p
(-8 + 2p + p2) + (p + -2)(p + 6) = 0

Reorder the terms:
-8 + 2p + p2 + (-2 + p)(p + 6) = 0

Reorder the terms:
-8 + 2p + p2 + (-2 + p)(6 + p) = 0

Multiply (-2 + p) * (6 + p)
-8 + 2p + p2 + (-2(6 + p) + p(6 + p)) = 0
-8 + 2p + p2 + ((6 * -2 + p * -2) + p(6 + p)) = 0
-8 + 2p + p2 + ((-12 + -2p) + p(6 + p)) = 0
-8 + 2p + p2 + (-12 + -2p + (6 * p + p * p)) = 0
-8 + 2p + p2 + (-12 + -2p + (6p + p2)) = 0

Combine like terms: -2p + 6p = 4p
-8 + 2p + p2 + (-12 + 4p + p2) = 0

Reorder the terms:
-8 + -12 + 2p + 4p + p2 + p2 = 0

Combine like terms: -8 + -12 = -20
-20 + 2p + 4p + p2 + p2 = 0

Combine like terms: 2p + 4p = 6p
-20 + 6p + p2 + p2 = 0

Combine like terms: p2 + p2 = 2p2
-20 + 6p + 2p2 = 0

Solving
-20 + 6p + 2p2 = 0

Solving for variable 'p'.

Factor out the Greatest Common Factor (GCF), '2'.
2(-10 + 3p + p2) = 0

Factor a trinomial.
2((-5 + -1p)(2 + -1p)) = 0

Ignore the factor 2.

Subproblem 1

Set the factor '(-5 + -1p)' equal to zero and attempt to solve: Simplifying -5 + -1p = 0 Solving -5 + -1p = 0 Move all terms containing p to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + -1p = 0 + 5 Combine like terms: -5 + 5 = 0 0 + -1p = 0 + 5 -1p = 0 + 5 Combine like terms: 0 + 5 = 5 -1p = 5 Divide each side by '-1'. p = -5 Simplifying p = -5

Subproblem 2

Set the factor '(2 + -1p)' equal to zero and attempt to solve: Simplifying 2 + -1p = 0 Solving 2 + -1p = 0 Move all terms containing p to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -1p = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -1p = 0 + -2 -1p = 0 + -2 Combine like terms: 0 + -2 = -2 -1p = -2 Divide each side by '-1'. p = 2 Simplifying p = 2

Solution

p = {-5, 2}

See similar equations:

| 3/4c+3=12 | | 1+u=(-6) | | 2n+(2n+1.2)=4n+(2n+0.1) | | 5x+14-8x=16-19x+16x-2 | | -2.7x=10.2 | | [2r-6]=21 | | 35+35*0+1= | | 6+(x+2y)i=x+4i | | x-5=11-7x-56 | | 4=k-(-10) | | (r-2t)(r+2t)= | | 2x+4x=4(x+16) | | 0.5(x-6)=7 | | 6a^2+28a+16= | | 4(z+2)=3(z-4)+z | | 4-2(x+3)=8x-14 | | -4x+27=147 | | 0.25x+0.20(270-x)=56.75 | | -4x+27=127 | | 10xq=8.7475 | | 4(2+v)+35v=13v | | -40=2-4x-3x | | 18-(4m+3)=4+4m-13 | | 8=x+7-2 | | -7y+18=123 | | 15=3-(z+10) | | 8n+12=3n+18 | | 4x+12=3x-12 | | B-18=(-13) | | 5x-1=x+6 | | -12q+n=-29 | | f(x)=x^2-4x-8 |

Equations solver categories